2018
DOI: 10.1080/16549716.2018.1477492
|View full text |Cite
|
Sign up to set email alerts
|

Impact of competitive foods in public schools on child nutrition: effects on adolescent obesity in the United States an integrative systematic literature review

Abstract: Background: The United States (US) is currently facing a public health crisis due to the percentage of obesity in adolescents. The Center for Disease Control (CDC) stated the risks for children due to obesity are many. Adolescents obtain a large portion of their daily caloric intake at school; therefore, what foods/drinks they are consuming is so serious. Objective: To identify and analyze literature on the effects of competitive foods in public schools on adolescent weight, or Body Mass Index (BMI), and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
(186 reference statements)
0
9
0
Order By: Relevance
“…Moreover, a review relying principally on cross-sectional studies indicated that shared family meals are associated with a lower obesity risk [ 33 ]. For the school environment, a negative influence of unhealthy food options on the weight of adolescents is being discussed; however, only very few studies to date have confirmed such a correlation [ 34 ]. For the living environment municipality, the availability of spaces that encourage physical activity [ 35 ], security of residential areas [ 36 ] and shopping and food options that promote a healthy diet [ 35 ] are considered to be factors that protect against obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a review relying principally on cross-sectional studies indicated that shared family meals are associated with a lower obesity risk [ 33 ]. For the school environment, a negative influence of unhealthy food options on the weight of adolescents is being discussed; however, only very few studies to date have confirmed such a correlation [ 34 ]. For the living environment municipality, the availability of spaces that encourage physical activity [ 35 ], security of residential areas [ 36 ] and shopping and food options that promote a healthy diet [ 35 ] are considered to be factors that protect against obesity.…”
Section: Resultsmentioning
confidence: 99%
“… [ 32 ] School food environment A balanced offer of food and meals at school can help prevent obesity. [ 33 ] Opportunities for physical activity at school Spaces and opportunities for physical activity at school can help prevent obesity. [ 34 ] Spaces for physical activity in the neighbourhood Spaces for physical activity in the neighbourhood (such as parks, sports facilities, playground) can help prevent obesity.…”
Section: Annex Tablementioning
confidence: 99%
“…Although TX Sprouts had excellent buy-in from elementary school principals and administrators, many of the schools permitted marketing or the sale of foods and beverages that contradicted the core messages being taught in the TX Sprouts intervention. There is inconclusive evidence that competitive food and beverage sources in schools promote poor dietary intake and some limited evidence to suggest that consumption of these foods is associated with higher Body Mass Index (BMI) and poorer weight outcomes in school children [ 54 , 55 , 56 ]. School wellness policies can integrate school gardening programs as part of the day-to-day culture to serve as a foundation for promoting health and wellness across a school’s campus.…”
Section: Discussionmentioning
confidence: 99%
“… 7–9 A smaller body of research has noted that the effectiveness of these policies in lowering overweight/obesity differed across gender, grade levels, school neighborhood socioeconomic status, or racial/ethnic groups. 10–17 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] A smaller body of research has noted that the effectiveness of these policies in lowering overweight/obesity differed across gender, grade levels, school neighborhood socioeconomic status, or racial/ ethnic groups. [10][11][12][13][14][15][16][17] Beyond individual characteristics, it is important to investigate how differences in place-level characteristics may interact with the food policies. Previous studies have shown differences in the availability of CF&B and in the presence of policies for promoting healthy lifestyles such as diet and physical activity by urbanicity.…”
mentioning
confidence: 99%